Mutualistic Synthesis from Orthogonal Dynamic Covalent Reactions - Lyu, Yonglei; Hu, Ying; Yang, Jinghui; Wang, Xin; Li, Jianwei (Angewandte Chemie, 2024)
Mutualisms are interactions that benefit all species involved. It has been widely investigated in neighbouring subjects, such as biology, ecology, sociology, and economics. However, such a reciprocal relationship in synthetic chemical systems has rarely been studied. Here, we demonstrate a mutualistic synthesis where byproducts from two orthogonal chemical reactions aid each other′s production. Disulfide exchange and hydrazone exchange were chosen to generate two dynamic combinatorial libraries. A minor tetrameric macrocycle from the active disulfide library was quantitatively amplified in the presence of the hydrazone library. This incorporation also turned on the previously inert hydrazone reaction, producing a linear species that formed a “handcuffs” catenane with the disulfide tetramer. These findings not only lend robust support to the hypothesis of “RNA‐peptide coevolution” for the origin of life but also broaden the scope of synthetic chemistry, highlighting the untapped potential of minor products from different reactions. Additionally, the co‐self‐assembly of these mutualistic entities to form supramolecular structures opens new avenues for future development of composite nanosystems with synergistic properties. We report a mutualistic synthesis concept via orthogonal chemical reactions: disulfide and hydrazone exchange. A tetrameric macrocycle from the active disulfide exchange catalyzed the otherwise inert hydrazone exchange, amplifying a linear hydrazone and forming “handcuffs” catenanes through noncovalent binding. The co‐amplification of both species resembles mutualism in ecosystems, as they were minor species when the reactions occurred independently.